Internet of things sensor network for indoor environmental quality monitoring (IEQMS) - Yeo, Dylan Zhi Wei (Nanyang Technological University, 2023)
Indoor Environmental Quality (IEQ) plays a vital role in our daily lives as it can affect the comfort and health of occupants within a building. Poor IEQ can lead to detrimental effects such as headaches and respiratory problem and reduction of productivity in the building. By monitoring of IEQ frequently, the presence of deteriorating IEQ have been detected and action can be taken to improve the IEQ in the building. With the rapid advancement of technology towards Internet of Things (IoT), it is now possible to develop a IoT sensor network for monitoring IEQ. The IoT sensor network will comprise of an IoT microcontroller and several compact sensors that is dedicated to monitor specific IEQ parameters in buildings with the aim of low cost and low power consumption. During this project, research was done to select a suitable IoT microcontroller and compact sensors to form an IoT sensor node. A supervisor node was also introduced to act as the bridge between the IoT sensor node and the internet. Various wireless communication protocols such as Wi-Fi and BLE were utilised as well for the communication between the nodes and the internet. The supervisor node would receive the data from the sensor node and upload the data to the internet and these data can be accessed through a cloud platform. The microcontroller used is the Arduino MKR WiFi 1010 microcontroller and was coded using the C++ programming language. This project details the steps in developing a IoT Sensor Network for Indoor Environmental monitoring and demonstrates the IoT sensor network architecture to showcase the transmission of data from the sensors to the Arduino IoT Cloud platform using the BLE and Wi-Fi wireless communication protocol, offering a comprehensive solution for IEQ monitoring.